Prevalence of IgA Nephropathy: A 10 Years' Experience from Jinnah Postgraduate Medical Centre, Karachi, Pakistan - Muhammad Ali; Shafique Ahmed; Ayesha Ejaz; Ghazala Usman; Abdul MananJunejo; Hina Iram; Moiz Ahmed (ziauddin University, 2024)
Background: Immunoglobulin A (IgA) is considered the most frequently dealt primary glomerulonephritis, worldwide. The Berger's disease or IgA nephropathy is a mesangial proliferative glomerulonephritis characterized by deposition of immunoglobulin A in kidneys. The aim of the study was to report the prevalence of IgA nephropathy and the associated parameters (age, gender, and body mass index) in our population. Methods: This was a retrospective study, accomplished at Jinnah Postgraduate Medical Centre, Karachi, Pakistan, from June 2009-May 2019. The histopathology and immunofluorescence of renal biopsies of 519 patients were studied and the prevalence of biopsy proven IgA nephropathy was determined. The Chi-square test was used for association of biopsy proven IgA nephropathy with age, gender, and body mass index. A p-value of 0.05 or less was considered statistically significant. Results: A total of 519 biopsies were studied, out of those, only 4 (0.8%) had IgA nephropathy with male dominance in the last 10 years at Karachi, Pakistan. Male to female ratio was found to be 3:1. The most common clinical indication for renal biopsy was isolated hematuria in 50% of the cases followed by acute kidney injury and nephritic syndrome with 25% each respectively. Most of the patients suffering from proteinuria (> 3.5gm/24 hours), microscopic hematuria in 80% cases, high blood pressure in 50% cases, with other associated symptoms including edema, gastrointestinal, and skin-related symptoms reported. Conclusion: Immunoglobulin A (IgA) nephropathy is not a commonly diagnosed glomerular lesion. Further large-scale cohorts can aid in determining the other factors associated with a low frequency of IgA nephropathy. Keywords: Biopsy; Glomerulonephritis; Immunoglobulin A; Nephropathy.